Meningkatkan Literasi dan Kreativitas Siswa Melalui Majalah Dinding (MADING) di SDN 06 Sungai Kayu Ara Kabupaten Siak - Sakur, Sakur; Julita, Sari; Simbolon, Parsiholan; Azmi, Muhammad Fiqri; Nabila, Rahma; Zulhendri, Zulhendri (Journal of Community Sustainability, 2025)
This research aims to increase student literacy and creativity at SD Negeri 06 Sungai Kayu Ara through the activity of making wall magazines (mading) with the theme "Heroes' Day". This activity was carried out by the UNRI 2024 Service Team by involving students in the process of creating poetry, short stories and pictures related to the theme of heroism. The research method used is descriptive with a qualitative approach, through data collection techniques in the form of observation, interviews, documentation. The research results showed that this activity was successful in increasing students' reading interest and writing skills, as well as stimulating their creativity in producing works of art and visual designs. Apart from that, this activity also strengthens students' understanding of heroic values and improves social skills through collaboration in making wall magazines. Overall, making wall magazines has proven to be effective in developing students' literacy and creativity, and can be used as a creative and fun alternative learning method in schools, especially in rural areas.